Simultaneous Determination of Losartan Potassium and Hydrochlorothiazide in Pure Form and in Tablets Using Octadecyl-Modified Aleppo Bentonite in TLC - Aziz Ramadan, Abdul; Bodakji, Amer; Mahmoud, Ibrahim (Asian Journal of Chemistry, 2011)
A new octadecyl-modified Aleppo bentonite (BAC18) in TLC was developed to determine losartan potassium and hydrochlorothiazide in pure form and tablets with mobile phase ammonium phosphate buffer (10 mmol L-1; pH 3.2 with orthophosphoric acid) and acetonitrile (60:40, v/v), at wavelength l = 260 nm. The particles of Aleppo bentonite with diameter less than 45 μm were treated by concentrated HCl (BA), after that grafted firstly by dimethyldichlorosilane, then secondly by Grignard reagent (octadecylmagensium bromide). The surface properties of octadecyl-modified bentonite were studied by nitrogen adsorption at 77 K, IR and NIR techniques. The retardation factors (Rf) of losartan potassium and hydrochlorothiazide were 0.266 and 0.757, respectively. Linearity for determination of losartan potassium and hydrochlorothiazide was in the range 1.00-10.0 μg/spot. The minimum determined concentration was 1.0 μg/spot for losartan potassium and hydrochlorothiazide with per cent relative standard deviation (RSD %) does not exceed 3.08 and 1.74 %, respectively. The limits of quantification (LOQ) were 0.85 and 0.72 μg/spot and the limits of detection (LOD) were 0.28 and 0.24 μg/spot for determination of losartan potassium and hydrochlorothiazide, respectively.